194k views
4 votes
Find dy/dx x=a(cost +sint) , y=a(sint-cost)​

User Rachvela
by
4.6k points

1 Answer

4 votes

Answer:


\begin{aligned} (dy)/(dx) &= (\cos(t) + \sin(t))/(\cos(t) - \sin(t)) \end{aligned} given that
a \\e 0 and that
\cos(t) - \sin(t) \\e 0.

Explanation:

The relation between the
y and the
x in this question is given by parametric equations (with
t as the parameter.)

Make use of the fact that:


\begin{aligned} (dy)/(dx) = \quad \text{$(dy/dt)/(dx/dt)$ given that $(dx)/(dt) \\e 0$} \end{aligned}.

Find
\begin{aligned} (dx)/(dt) \end{aligned} and
\begin{aligned} (dy)/(dt) \end{aligned} as follows:


\begin{aligned} (dx)/(dt) &= (d)/(dt) [a\, (\cos(t) + \sin(t))] \\ &= a\, (-\sin(t) + \cos(t)) \\ &= a\, (\cos(t) - \sin(t))\end{aligned}.


\begin{aligned} (dx)/(dt) \\e 0 \end{aligned} as long as
a \\e 0 and
\cos(t) - \sin(t) \\e 0.


\begin{aligned} (dy)/(dt) &= (d)/(dt) [a\, (\sin(t) - \cos(t))] \\ &= a\, (\cos(t) - (-\sin(t))) \\ &= a\, (\cos(t) + \sin(t))\end{aligned}.

Calculate
\begin{aligned} (dy)/(dx) \end{aligned} using the fact that
\begin{aligned} (dy)/(dx) = \text{$(dy/dt)/(dx/dt)$ given that $(dx)/(dt) \\e 0$} \end{aligned}. Assume that
a \\e 0 and
\cos(t) - \sin(t) \\e 0:


\begin{aligned} (dy)/(dx) &= (dy/dt)/(dx/dt) \\ &= (a\, (\cos(t) + \sin(t)))/(a\, (\cos(t) - \sin(t))) \\ &= (\cos(t) + \sin(t))/(\cos(t) - \sin(t))\end{aligned}.

User Stefan Matei
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.